O papel da capacidade absortiva na inovação aberta voltado às tecnologias da indústria 4.0: um estudo nas indústrias de manufatura no Rio Grande do Sul - Bosa, Igor (2022)
The study aimed to analyze the impact of companies' absorptive capacity on open innovation in production processes aimed at adapting to Industry 4.0. Initially, a systematic literature review was conducted to clarify the relationship between the concepts of open innovation and absorptive capacity. It was identified that there was no consensus among the authors who address the subject. Existing research in the area has not yet been able to understand how each of the dimensions of absorptive capacity relates to open innovation, since there are studies that indicate that only potential absorptive capacity affects open innovation, while other studies show that only realized absorptive capacity is related to open innovation. To fill this gap, we sought to better understand this relationship. Given the importance of companies innovating to remain more competitive and the transition of industries to the Industry 4.0 model, this study sought to evaluate this relationship in a context of process innovation aimed at adapting industries to the Industry 4.0 model. The results obtained through structural equation modeling suggest that, within the scope of adaptation to the Industry 4.0 model, the openness of companies' innovation process allows them to accumulate more knowledge related to it. Furthermore, the results suggest that only the dimensions of absorptive capacity that make up the realized absorptive capacity (transformation and exploration) mediate the relationship between innovation openness and the degree of knowledge about Industry 4.0.